Diversity and biology of Spirometra tapeworms (Cestoda: Diphyllobothriidea), zoonotic parasites of wildlife: A review - Kuchta, Roman; Phillips, Anna J; Scholz, Tomáš (International journal for parasitology. Parasites and wildlife, 2024)
Tapeworms of the genus Spirometra Faust, Campbell et Kellogg, 1929 have long been known as intestinal parasites of carnivores and their larvae (spargana) have been found in various vertebrates. Nevertheless, their species diversity, host associations and geographical distribution remain poorly understood. Molecular data clearly confirm the validity of the genus, which has been synonymised by several authors with Diphyllobothrium Cobbold, 1858. Despite morphological similarities between the species of the two genera, they are not closely related and also differ in their life cycle. The present review provides a list of the species recognised as valid and additional genotypes that may represent other species, with a basic characterisation of each taxon and comments on their validity, the probable range of definitive and intermediate hosts, and their distribution. The existing taxonomic problems and the insufficient knowledge of the host specificity and distribution of Spirometra tapeworms can only be solved by combining molecular and morphological data, i.e. by comparing genetically characterised specimens with corresponding morphological vouchers (hologenophores). Further targeted sampling and surveys are required to clarify the distribution and host associations.
Keywords: Geographical distribution; Molecular phylogeny; Sparganosis; Broad tapeworms; Diversity; Zoonosis; Host range